Extraction Of y-Oryzanol And Tocopherols From Rice (Oryza Sativa) Bran - Ismail, Rosnizam (2008)

(untitled)
The objective of this study was to extract y-oryzanol and tocopherols from rice bran. Different extraction times and sequential extractions utilizing different solvents on y- oryzanol and tocopherols levels from crude rice bran oil (CRBO) were studied. Rice bran was extracted using hexane with five different extraction times, while sequential extractions was carried out utilizing hexane, hexane/dichloromethane, dichloromethane and dichloromethane/methanol. Extraction of y-oryzanol and tocopherols was further studied using precipitation and liquid-liquid separation from unsaponified fraction of CRBO. Precipitation was carried out by diluting the sample in hexane overnight at -20˚C. Liquid-liquid separations were carried out using hexanemethanol or hexane-acetonitrile. Solid and liquid portions formed from precipitation were further separated by liquid-liquid separations. The final stage of the extraction process was a combination of precipitation and single-stage chromatographic separation. Results showed that percentage of extracted oil was not significantly different with the different extraction times used. However, 20 min extraction resulted in the highest y-oryzanol level (p<0.05). On the other hand, 30 min extraction gave the highest tocopherols level (p<0.05). Sequential extractions resulted in higher y- oryzanol and tocopherols levels than that of hexane extraction alone (p<0.05). After saponification of CRBO extraction (with hexane, hexane/dichoromethane and dichloromethane), the unsaponified fraction was found to contain 1.4% y-oryzanol and 0.02% tocopherols. In liquid-liquid separations on unsaponified fraction of CRBO study, the process was able to concentrate 2.1% y-oryzanol in methanol and 1.8% in acetonitrile, respectively. On the other hand, 0.03% tocopherols was concentrated in methanol and 0.04% in acetonitrile, respectively. In precipitation study, 4.04% y- oryzanol was concentrated in solid portion. In column chromatography study, combining precipitation and single stage silica chromatography was able to concentrate 10.99% y-oryzanol and 0.02% tocopherols. This work proposed an alternative method for y-oryzanol and tocopherols extraction from rice bran.